THE EFFECT OF CORRUPTIVE SITUATIONS ON THE DEVELOPMENT OF CIVIL SOCIETY - Toshpo‘latov Jamshidbek Tohirjon o‘g‘li (Modern American Journals, 2025)
This article is about corruption, i.e. bribery. Information is given about the existence of corruption in history and the punishment used against it, as well as the experiences of the countries of the world against bribery. The measures and laws adopted against this in Uzbekistan are shown.
Keywords: Corruption, vice, history, law, world experience, Singapore, China, Hong Kong, Denmark, UN.